조리조건에 따른 은행알의 4"-O-methylpyridoxine (ginkgotoxin) 함량 및 항산화 활성 변화 - 홍서정(Seo Jung Hong); 장진아(Jin A Jang); 황현정(Hyun Jung Hwang); 조미숙(Mi Sook Cho) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2017)
The purpose of this study was to examine the best cooking condition to decrease 4'-O-methylpyridonxine (MPN, ginkgotoxin) and increase the antioxidative effect. We also examined the change in color of ginkgo biloba seeds after different cooking methods and times. MPN content was decreased with an increase in the cooking time. For the reduction of MPN content, the most efficient cooking method was pan-frying. In particular, MPN content was largely reduced after 8 min of pan-frying. 1,1-Diphenyl-2-picrylhydrazyl radical scavenging activity and total flavonoid content were increased after 11 min of pan-frying and this level was maintained until 14 min. The total phenolic compound content was maintained for up to 30 min by steaming and 11 min by pan-frying. Therefore, the optimum condition was established by pan-frying from 8 to 11 min.